2020
DOI: 10.1103/physrevb.101.214417
|View full text |Cite
|
Sign up to set email alerts
|

Field evolution of low-energy excitations in the hyperhoneycomb magnet βLi2IrO3

Abstract: Li nuclear magnetic resonance and terahertz (THz) spectroscopies are used to probe magnetic excitations and their field dependence in the hyperhoneycomb Kitaev magnet β-Li 2 IrO 3. Spin-lattice relaxation rate (1/T 1) measured down to 100 mK indicates the gapless nature of the excitations at low fields (below H c 2.8 T), in contrast to the gapped magnon excitations found in the honeycomb Kitaev magnet α-RuCl 3 at zero applied magnetic field. At higher temperatures in β-Li 2 IrO 3 , 1/T 1 passes through a broad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 41 publications
5
13
0
Order By: Relevance
“…Also, this continuum contribution was not seen in the terahertz measurements of Ref. [54] because these only captured spectra up to ∼10 meV.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, this continuum contribution was not seen in the terahertz measurements of Ref. [54] because these only captured spectra up to ∼10 meV.…”
Section: Discussionmentioning
confidence: 98%
“…β-Li 2 IrO 3 is perhaps the most intriguing example of the complex interplay between the Kitaev exchange and external magnetic fields [52][53][54]. At zero field, the system orders at T I = 38 K into a complex incommensurate order (IC) with counter-rotating spirals and propagation wave vector Q = (0.574, 0, 0); all Q vectors are reported in orthorhombic reciprocal lattice units [31].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these materials exhibit complex long-range magnetic orders at sufficiently low temperatures, indicating that other subdominant interactions between magnetic moments are present and may also have nontrivial bond-dependent character. Both experiment [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and theory [27][28][29][30][31][32][33] have shown that these orders are fragile and can be efficiently suppressed by external magnetic field. It was also found that the competition between the external field and anisotropic bond-dependent exchange interactions gives rise to highly anisotropic magnetization processes and a variety of complex orders at intermediate fields [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the purpose of this paper is to understand the recent torque measurements in β-Li 2 IrO 3 [26] and γ -Li 2 IrO 3 [12,13]. These two materials appear to have closely related local energetics [35], and we will therefore focus entirely on the hyperhoneycomb β-Li 2 IrO 3 [23][24][25][26]36,37], whose microscopic minimal model, the nearest-neighbor (NN) J-Kmodel, has been better understood [30,31,[38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…These parameters are only marginally different from the ambient-pressure values obtained using the same superexchange theory (K = −12.1 meV, Γ = −13.5 meV, and J = −4.8 meV [19]). Experimentally, one finds |K| ≃ |Γ| ≃ 13 meV [18,35] and J ≃ 0.3 meV [36]. Exact diagonalization for the Ir1-Ir3-Ir3-Ir1 tetramer was performed in Mathematica using exchange parameters for the partially dimerized phase.…”
Section: Magnetismmentioning
confidence: 99%